Fault mechanics and post-seismic deformation at Bam, SE Iran. Issue 2 (21st February 2017) - Wimpenny, Sam; Copley, Alex; Ingleby, Tom
Summary: The extent to which aseismic deformation relaxes co-seismic stress changes on a fault zone is fundamental to assessing the future seismic hazard following any earthquake, and in understanding the mechanical behaviour of faults. Here we use models of stress-driven afterslip and viscoelastic relaxation, in conjunction with post-seismic InSAR measurements, to show that there has been minimal release of co-seismic stress changes through post-seismic deformation following the 2003 M w 6.6 Bam earthquake. Our analysis indicates the faults at Bam remain predominantly locked, suggesting that the co- plus interseismically accumulated elastic strain stored downdip of the 2003 rupture patch may be released in a future M w 6 earthquake. Our observations and models also provide an opportunity to probe the growth of topography at Bam. We find that, for our modelled afterslip distribution to be consistent with forming the sharp step in the local topography over repeated earthquake cycles, and also to be consistent with the geodetic observations, requires either (1) far-field tectonic loading equivalent to a 2–10 MPa deviatoric stress acting across the fault system, which suggests it supports stresses 60–100 times less than classical views of static fault strength, or (2) that the fault surface has some form of mechanical anisotropy, potentially related to corrugations on the fault plane, that controls the sense of slip.